Acupuncture Treatment in Elderly People with Sarcopenia: Effects on the Strength and Inflammatory Mediators - Gisele Soares Mendes Damasceno; Thaís Helena Machado Marçal Teixeira; Vinicius Carolino de Souza; Tiago Sousa Neiva; Karina Prudente Pereira; Maria de Fátima Teles Landim; Gislane Ferreira de Melo; Juliana de Faria Fracon e Romão; Otávio Tolêdo Nóbrega; Gustavo de Azevedo Carvalho (Journal of Aging Research)
Introduction. Sarcopenia is defined as the progressive loss of skeletal muscle mass, associated with aging. A multidisciplinary approach has been increasingly prioritized in elderly care. A technique that has been widely used by the seniors is acupuncture. Objectives. To analyse the effects of acupuncture in muscle strength and in inflammatory markers of older people with sarcopenia. Methods. The sample was composed by 53 elderly people, aged over 60 years. Inclusion criteria were as follows: male and female seniors, sedentary and who were not under acupuncture treatment during the survey period. Assessment of body composition, handgrip strength, and functional test and IL-6, IL-10, and TNF-α cytokines analyses were performed. After verification of the physical examination, the subjects were divided into two groups (sarcopenic and nonsarcopenic). The first group was then randomized (by drawing lot) to be further divided into two subgroups: G1, composed of sarcopenic elderly people who received acupuncture intervention, and G2, composed of sarcopenic elderly people who did not receive intervention. The nonsarcopenic elderly people composed the group 3 (G3) and did not receive acupuncture intervention. ANOVA Split Plot was performed for intergroup comparison. For intragroup evaluation, ANOVA was conducted for repeated measures. For the delta values, ANCOVA was performed with the pretest as covariant. A p<0.05 significance level was adopted. Results. 26 older people concluded the collections. There was no statistically significant difference between the G1 group and the other ones regarding the assessed variables (muscle mass, muscle strength, functionality, and inflammatory markers). Conclusion. The results allow us to infer that it is possible that the conducted intervention protocol has not produced any significant effects in the studied population. UTN number: RBR-8df2h4.